‘This funny place’: Uncovering the ambiguity of saltmarshes using a multimodal approach - Erin Roberts (People and Nature, 2022)
Saltmarshes are increasingly recognised for the range of benefits they offer, including coastal protection, flood regulation and carbon sequestration. However, much less is known about how people perceive these environments and their importance for non-material aspects of human well-being.As climate change and sea-level rise render these environments increasingly vulnerable, there is a need to better understand how saltmarshes are valued. This is because these values influence—and are influenced by—the ways in which people interact with places and therefore gain well-being benefits from them. These values also shape management decisions, which in turn affect the well-being of people and environment.To address this need, we use a multimodal qualitative approach (mobile interviews, photo elicitations, mapping and word association) to explore the values held in connection to saltmarshes at two Welsh case study sites: the Taf Estuary in Carmarthenshire and the Mawddach Estuary in Gwynedd.We find that saltmarshes are ambiguous places, not having one obvious meaning, and being open to more than one interpretation. They are both known and unknown; valued and (literally) overlooked. We suggest that this ambiguousness is related to both the physical characteristics of saltmarshes, which change and shift on short and long time-scales, as well as to the ways in which people (can) relate with them.We discuss how ambiguity renders saltmarshes as places of exclusive, privileged human–nature relationships, and reflect on the implications of our findings for human well-being and the management of threatened environments. We also consider how multimodal, in-depth and place-based methods such as ours provide ways in which to explore the more intangible and changeable values associated with particular habitats.